The Effect of Flipped Classroom Size on Students' Critical Thinking Abilities - Everhard Markiano Solissa; Agus Triyono; Dharma Gyta Sari Harahap; Dewi Maharani Rachmaningsih; Novinaty Djafri; Asmawati Asmawati; Tomi Apra Santosa (Universitas Muhammadiyah Enrekang, 2023)
purpose of this research is to determine the effect of flipped classroom size on students' critical thinking abilities. This type of research is meta-analysis. The data source comes from an analysis of 12 national and international journals published in 2018-2023. Data source search process via Google Scholar; ERIC, ScienceDirect, Wiley; ProQuest, DOAJ and EBSCO. Data selection using the PRISMA method consists of identification, screening, eligibility and inclusion. These findings conclude that the flipped classroom has a positive influence on students' critical thinking skills with a summary effect size value ( rRE= 0.799). The flipped classroom has a moderate influence on students' critical thinking abilities at school